A new formula to predict buckling pressure of steel ellipsoidal head under internal pressure. (November 2019) - Li, K.; Zheng, J.; Zhang, Z.; Gu, C.; Xu, P.; Chen, Z.
Abstract: Buckling is a critical failure mode of ellipsoidal head under internal pressure. This study focuses on the prediction of buckling pressure of steel ellipsoidal heads subjected to internal pressure. First, finite element model of ellipsoidal head is generated, taking into account the effects of material and geometrical nonlinearity. The plastic bifurcation buckling pressure of ellipsoidal head is determined by nonlinear FEM. Second, we study the effects of diameter-thickness ratio, radius-height ratio, yield strength, strain hardening and attached cylinder on buckling pressure. Based on FE results of the models with elastic-perfectly plastic material, we propose a formula to predict buckling pressure of perfect ellipsoidal head. In addition, we summarize experimental results on the buckling of twenty-one ellipsoidal heads which cover different geometrical parameters, material types, and methods of fabrication. Eleven out of twenty-one ellipsoidal heads were tested by the authors recently. Finally, based on the formula for perfect ellipsoidal heads, a new formula is developed for the buckling pressure of actual ellipsoidal heads after considering a reduction factor that accounts for the effect of initial shape imperfection. The reduction factor depends on the methods of head fabrication, i.e. whether cold pressing and spinning or assembly of formed segments. It is shown that the new formula has comprehensive advantage in accuracy and applicability in comparison with other formulae. Highlights: Nonlinear FEM is used to simulate plastic bifurcation buckling behavior. Buckling experiment is performed on eleven ellipsoidal heads. A new formula to predict buckling pressure is proposed.